A Cross-Sectional Study of Nemaline Myopathy. (9th March 2021) - Amburgey, Kimberly; Acker, Meryl; Saeed, Samia; Amin, Reshma; Beggs, Alan H.; Bönnemann, Carsten G.; Brudno, Michael; Constantinescu, Andrei; Dastgir, Jahannaz; Diallo, Mamadou; Genetti, Casie A.; Glueck, Michael; et al.
Abstract : Objective: Nemaline myopathy (NM) is a rare neuromuscular condition with clinical and genetic heterogeneity. To establish disease natural history, we performed a cross-sectional study of NM, complemented by longitudinal assessment and exploration of pilot outcome measures. Methods: Fifty-seven individuals with NM were recruited at 2 family workshops, including 16 examined at both time points. Participants were evaluated by clinical history and physical examination. Functional outcome measures included the Motor Function Measure (MFM), pulmonary function tests (PFTs), myometry, goniometry, and bulbar assessments. Results: The most common clinical classification was typical congenital (54%), whereas 42% had more severe presentations. Fifty-eight percent of individuals needed mechanical support, with 26% requiring wheelchair, tracheostomy, and feeding tube. The MFM scale was performed in 44 of 57 participants and showed reduced scores in most with little floor/ceiling effect. Of the 27 individuals completing PFTs, abnormal values were observed in 65%. Last, bulbar function was abnormal in all patients examined, as determined with a novel outcome measure. Genotypes included mutations in ACTA1 (18), NEB (20), and TPM2 (2). Seventeen individuals were genetically unresolved. Patients with pathogenic ACTA1 and NEB variants were largely similar in clinical phenotype. Patients without genetic resolution had more severe disease. Conclusion: We present a comprehensive cross-sectional study of NM. Our data identify significant disabilities and support a relatively stable disease course. We identify a need for further diagnostic investigation for the genetically unresolved group. MFM, PFTs, and the slurp test were identified as promising outcome measures for future clinical trials.